Trends in Biology, Geology & Environmental Education Research in the Czech Republic from 2008 to 2018 - Kroufek, Roman; Jáč, Martin; Janštová, Vanda; Pražáková, Martina; Čiháková, Kateřina (Scientia in educatione, 2020)
The primary objective of the study is to describe trends in Czech Biology, Geology & Environmental Education Research in the period 2008 – 2018. The secondary objective is to compare these trends with findings made by foreign authors in the analysis of national and international research in science education, especially biology. To achieve this goal, a content analysis of 148 texts of the given topic published in journals with standard review procedures was performed. Most contributions were published in the journals Envigogika and Scientia in educatione, which focus directly on environmental education and science education, respectively. In the analyzed texts, research with quantitative design prevailed and the respondents were mostly lower-secondary school pupils. Theoretical studies are underrepresented in the Czech environment, as well as studies on the curriculum. Research articles were relatively often devoted to evaluation or inquiry-based science education. The good news for the Biology & Geology and Environmental Education Research community is, besides the tradition of professional conferences and the existence of two doctoral degree programs, the fact that the focus of research does not substantially differ from international trends.